Proteomic Analysis of the Fish Pathogen Vibrio ordalii Strain Vo-LM-18 and Its Outer Membrane Vesicles - Macarena Echeverría-Bugueño; Mauricio Hernández; Ruben Avendaño-Herrera (Animals)
Vibrio ordalii is the causative agent of atypical vibriosis in salmonids cultured in Chile. While extensive research provides insights into V. ordalii through phenotypic, antigenic, and genetic typing, as well as various virulence mechanisms, proteomic characterization remains largely unexplored. This study aimed to advance the proteomic knowledge of Chilean V. ordalii Vo-LM-18 and its OMVs, which have known virulence. Using Nano-UHPLC-LC-MS/MS, we identified 2242 proteins and 1755 proteins in its OMVs. Of these, 644 unique proteins were detected in V. ordalii Vo-LM-18, namely 156 unique proteins in its OMVs and 1596 shared proteins. The major categories for the OMVs were like those in the bacteria (i.e., cytoplasmic and cytoplasmic membrane proteins). Functional annotation identified 37 biological pathways in V. ordalii Vo-LM-18 and 28 in its OMVs. Proteins associated with transport, transcription, and virulence were predominant in both. Evident differences in protein expression were found. OMVs expressed a higher number of virulence-associated proteins, including those related to iron- and heme-uptake mechanisms. Notable pathways in the bacteria included flagellum assembly, heme group-associated proteins, and protein biosynthesis. This proteomic analysis is the first to detect the RTX toxin in a V. ordalii strain (Vo-LM-18) and its vesicles. Our results highlight the crucial role of OMVs in the pathogenesis and adaptation of V. ordalii, suggesting use as potential diagnostic biomarkers and therapeutic targets for bacterial infections.